A Trial Study of Moxibustion with a Warming Needle on Edema - Wen-Ping Zhang; Yuki Onose; Takahiko Fujikawa (Medical Association of Pharmacopuncture Institute, 2017)
Edema is an accumulation of an excessive amount of watery fluid in cells or intercellular tissues. In order to examine the effects of acupuncture and moxibustion on edema, seven subjects were randomly divided into three groups, that was a Control group, an Acupuncture group (Acp), and an acupuncture and moxibustion group (Acp-Mox). After sitting for 60 minutes keeping their bodies still, the Acp and Acp-Mox subjects were administered acupuncture or acupuncture/moxibustion on the points of Zusanli (ST-36) and Sanyinjiao (SP-6), separately as against the Control group who only lied on the bed after modelization. After modelization at 60 minutes, the skin temperature and blood flow of all the groups were significantly lower in blood flow when compared with premodelization. But shortly after the procedure at 80 minutes, skin temperature in the Acp and Acp-Mox groups were significantly increased when compared with premodelization (vs. 60 minutes, p < 0.05). Moreover, the skin temperature and blood flow of the Acp-Mox group were significantly increased as compared to both the Control and the Acp group at the 80-minute time point. These results indicate that Acp and Mox-Acp could relieve edematous conditions significantly, especially the procedure of moxibustion with warming needle, was effective in improving edema which is often accompanied with cold intolerance and would be a recommended and superior therapy for edema.